Features of Parents’ Attitude to Junior Students with Mental Retardation - Kovalishin, I. V. (Psychological Prospects Journal, 2012)
The article represents theoretical and practical analysis of parents’ attitude to children with mental retardation. Results of research are described using specially selected methods and techniques. The basic characteristics that relate to features of education in this category of children are allocated.
Keywords: family mental retardation junior school age parents’ attitude education «parents-children» relations